POLA PERTUMBUHAN IKAN KAKAP MERAH (LUTJANUS TIMORIENSIS) DI PPI LHOK BENGKUANG, KABUPATEN ACEH SELATAN GROWTH PATTERN OF FISH RED SNAPPER (LUTJANUS TIMORIENSIS) AT PPI LHOK BENGKUANG, REGENCY SOUTH ACEH - Ila, Nyak; Mursawal, Asri (Jurnal Laot Ilmu Kelautan, 2023)
AbstractRed snapper is a type of reef fish that has high value, so it is necessary to research on the growth pattern of red snapper to determine the growth pattern landed at PPI Lhok Bengkuang. This study aims to determine the growth pattern of red snapper landed by fishermen at PPI Lhok Bengkuang. In order to know the growth pattern of L. timoriensis through the long-weight relationship of the fish from the growth aspect of the fish's weight and length. The research was conducted in October–November 2022 at PPI Lhok Bengkuang, South Aceh District. The research method was proportional random sampling and then the data were analyzed using linear regression. The number of individual samples whose growth patterns were analyzed was 30 individuals with the type of species L. timoriensis. Total body length ranges from 22.4 cm-30.3 cm and body weight ranges from 161 grams-455 grams. The results of the regression analysis on L. timoriensis individuals obtained a regression value (b) of 0.0989391 with a coefficient of determination (R2) of 0.7180290 which indicates that the weight gain is 72%. The value of b = 0.0989391 means that it is smaller than the normal b value, it is called a negative allometric growth pattern, that is, the length relationship is faster than the weight of the fish. On the growth pattern of L. timoriensis, it is necessary to carry out further research with a longer time and a larger number of samples to obtain more complete data and information.